Psychosocial Hazard Awareness: Health and Non-Health Workers in Semarang Dental, Oral Hospitals - Prasetio, Diki Bima; Sahiroh, Eli; Putri, Nasya Adelia; Pramesti, Shinta Dwi Surya; Setyaningsih, Yuliani; Lestari, Sri; Arti, Dwi Windu Kinanti; Bayusunuputro, Billy Zia Napoleon (Sekolah Vokasi Universitas Gadjah Mada, 2025)
Background: Psychosocial hazards are one of the risks that affect the mental health of hospital workers..Objective: This study aimed to assess awareness of psychosocial hazards in health and non-health workers at Dental and Oral Hospitals in Semarang.Methods: This cross-sectional study involved 154 respondents using a Psychosocial Survey of Healthcare Workers questionnaire that was adapted in Indonesian, covering 12 dimensions. The independent variables were age, gender, years of service, unit section, education level, and marital status, while the dependent variable was psychosocial hazard awareness.Results: The results showed that 57.1% of respondents had a good level of awareness of psychosocial hazards. Chi-square analysis showed a significant relationship between age (p=0.006), working period (p=0.002), education level (p=0.020), and marital status (p=0.043) and the level of awareness of psychosocial hazards, while gender and work unit showed no significant relationship. The results of the multivariate test with multiple logistic regression revealed the most significant factors, namely age (0.004) and education level (0.020).Conclusion: This awareness was important to prevent fatigue and mental disorders. Efforts to increase education about psychosocial hazards in the work environment were needed as a preventive measure to maintain the mental health of hospital workers.